Acid Fast Positivity Rate and Associated Factors of Leprosy in a Tertiary Care Hospital of Northeastern Ethiopia: Its Implication for Evidence‐Based Leprosy Prevention and Control - Alemu Gedefie; Agumas Shibabaw; Zewudu Mulatie; Hussen Ebrahim; Habtu Debash; Mihret Tilahun; Ermiyas Alemayehu; Melaku Ashagrie Belete; Ousman Mohammed; Saba Gebremichael Tekele; Daniel Gebretsadik Weldehanna; Bruktawit Eshetu (Health Science Reports)
ABSTRACT Background and Aim Leprosy is one of the most common skin neglected tropical diseases in Ethiopia posing social stigma, physical disability, deformity, discrimination, loss of social status, and poor quality of life in families. Hence, evidence‐based collaborative inter‐sectoral actions should be performed to reduce and eliminate its burden in endemic areas. Thus, the aim of this study was to assess the acid‐fast positivity rate and associated factors of leprosy among suspected cases in Northeastern Ethiopia: a cross‐sectional study. Method A cross‐sectional study was conducted from September 2022 to March 2023 among 256 leprosy‐suspected cases selected using a simple random sampling technique. A semi‐structured questionnaire was used to collect socio‐demographic, clinical, and predictor variables of leprosy through face‐to‐face interviews. Skin slit specimens were collected and stained using Ziehl–Neelsen staining technique. STATA 17 was used for analysis. The scale reliability coefficient was checked using Cronbach's α and the goodness‐of‐fit test of the model was assessed by the Hosmer–Lemshow test. Moreover, bivariable and multivariable logistic regression were computed. Finally, variables with an adjusted odds ratio and their p < 0.05 were taken as statistically significant. Result The mean ± standard deviation of the age of participants was 43.25 ± 16.35. The overall, prevalence of acid‐fast positivity among suspected cases was 19.6% (95% CI: 15.8%, 23.4%). Multivariable logistic regression analysis showed that sex being male (p = 0.045), rural residence (p = 0.047), not eating three times meals frequency (p = 0.014), not eating a balanced diet (p = 0.036), poor personal hygiene (p = 0.028), distant from health facility (p = 0.039), not washing hands usually (p = 0.013), presence of current co‐infection (p = 0.002), type of leprosy (p = 0.004), and close contact with leprosy cases (p = 0.003) were more likely to be positive for leprosy. Conclusion The prevalence of leprosy was remained high. Thus, early detection and treatment are necessary to reduce delayed diagnosis and hidden transmission of leprosy in the community. By addressing the driving factors through evidence‐based intervention, we can significantly control the burden of leprosy in the affected communities, and improve their health outcomes and quality of life.